2018
DOI: 10.1007/s10266-018-0358-1
|View full text |Cite
|
Sign up to set email alerts
|

The higher prevalence of developmental defects of enamel in the dioxin-affected region than non-dioxin-affected region: result from a cross-sectional study in Vietnam

Abstract: Developmental defects of enamel (DDE) are induced and regulated by several factors including genetics and the environment. There is evidence showing that dioxin in polluted areas has a strong effect on the health and development of teeth. However, there has been no study on DDE in the dioxin-affected regions in Vietnam. To identify the effect of dioxin on the prevalence of DDE in studied areas in Vietnam, a cross-sectional study was conducted in 2200 adults in the A Luoi district in the Thua Thien Hue province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Ngoc et al (2019) performed a case–control study to investigate the effects of PCDD/Fs on the prevalence of enamel dysplasia in 2200 adults living in herbicide-sprayed and non-sprayed areas in Viet Nam [ 22 ]. The results indicated that enamel dysplasia occurred in 20.5% and 5.8% of adults living in the sprayed areas and the non-sprayed areas, respectively, suggesting that enamel dysplasia was almost twice as prevalent in the exposed population than in the control population [ 22 ]. Enamel dysplasia was more prevalent in the premolars than in the molars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngoc et al (2019) performed a case–control study to investigate the effects of PCDD/Fs on the prevalence of enamel dysplasia in 2200 adults living in herbicide-sprayed and non-sprayed areas in Viet Nam [ 22 ]. The results indicated that enamel dysplasia occurred in 20.5% and 5.8% of adults living in the sprayed areas and the non-sprayed areas, respectively, suggesting that enamel dysplasia was almost twice as prevalent in the exposed population than in the control population [ 22 ]. Enamel dysplasia was more prevalent in the premolars than in the molars.…”
Section: Resultsmentioning
confidence: 99%
“…Enamel dysplasia was more prevalent in the premolars than in the molars. Most lesions were found on the buccal surfaces of the teeth [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical elements may cause an adverse effect on dental formation. An association appears to exist between aDDE and some toxins: radioactive contamination ( 120 ), dioxin exposure ( 121 ) (“Agent Orange”), chronic lead poisoning ( 122 ), and long- term exposure to PCBs ( 123 ) and excess fluoride ( 124 ).…”
Section: Methodsmentioning
confidence: 99%
“…1,3,[7][8][9] The collected data were checked and analyzed by using statistical program SPSS (version 23.0, SPSS Inc., Chicago). 11,12 All variables were in a normal distribution with Kolmogorov-Smirnov test and normal quantile plots (data no shown). The two independent samples were analyzed using student's T-test, while multiple samples were analyzed using one-way ANOVA.…”
Section: Instead Of Formula: N = 313 Childrenmentioning
confidence: 99%